Analisis Pelatihan dan Pengembangan Sumber Daya Manusia (Study Kasus: PT. BTPN Tbk Kantor Cabang Jambi) - Mustika Mustika; Indri Apriani (Universitas Batanghari Jambi, 2021)
The purposes of this study are 1) To find out the types of training and HR development carried out at Bank BTPN tbk Jambi Branch Office, 2) To find out the constraints and solutions for HR training and development carried out at Bank BTPN tbk Jambi Branch Office, 3 ) To know the Strategy of Training and Human Resources Development at Bank BTPN tbk Jambi Branch Office. This study took place at Bank BTPN tbk Jambi Branch Office, the data obtained directly from books or other information in the form of interviews and documentation. The data collection method was obtained by direct observation at the Human Resources section at PT. Bank BTPN Jambi Branch Office. This study uses a qualitative descriptive method that is